Femoral migration of the cementless Oxford which caused the bearing dislocation: a report of two cases - Inui, Hiroshi (BMC Musculoskelet Disord, 2020)
BACKGROUND: There are no previous reports on the complications around the femoral component of cementless Oxford unicompartmental knee arthroplasty (UKA). However, we experienced two cases of femoral migration to the proximal side, which caused bearing dislocations after cementless Oxford UKA. CASE PRESENTATION: Case1. In an 82-year-old woman, bearing dislocation occurred 13 months postoperatively because of femoral migration that was resolved with an revision surgery to cemented component and thicker mobile insert. Case2. In a 52-year-old man, first bearing dislocation occurred 7 months postoperatively. Five months after revising the insert to a thicker one, another dislocation occurred mainly because of the femoral migration. Eventually, a revision to total knee arthroplasty was necessary. CONCLUSIONS: The inferred main reasons of femoral migration of cementless Oxford were osteoporosis for the first case and early return to high performance sports activity for the second case. Although several merits of using cementless prosthesis, particularly better fixation and lesser radiolucency than cemented prosthesis, have been reported, surgeons should pay attention to the patient’s bone quality and advise a slow return to high-level physical activity.